Welfare of dairy cows in compost barn systems (Veterinary Science, 2022)
Confined milk production systems can present several critical points with respect to animal welfare, which does not imply that they cannot be resolved. Housing dairy cattle in compost barns, with proper design and management, has been shown to improve cow health and longevity and, consequently, their productive performance. Based on the results carried out worldwide, the compost barn systems represent a friendly housing alternative with the well-being of the animals compared to other confinement systems. However, the number of investigations on the welfare of dairy cattle in these systems in Argentina and in the world is still scarce, so it would be advisable to add regional studies to be able to precede in terms of the real and potential impact on dairy cows.
Keywords: Dairy; Housing; Compost barn; Management; Animal welfare